La canción Alla sua donna: el platonismo paradójico de Giacomo Leopardi - Coriasso Martín-posadillo, Cristina (Cuadernos de Filología Italiana, 2007)
According to the different critical contributions, the Leopardian song Alla sua donna, where the presence of the platonist, stilnovistic and petrarchean tradition is essential, can be considered an exercise of defamiliarization and irony of the Italian lyrical tradition, and at the same time like an exaltation of the sublimation from the disillusion; or can be interpreted, and this is our thesis following Rigoni, Galimberti y Cacciari, like a privileged expression of the paradoxical platonism that is in all the Leopardian thought. The Idea of the Eternal Feminine is the theme of this song, according with the theory of Kant in the Critique of the judgement, despite the abysmal distance that, under other aspects, separates Leopardian from Kantian thought, but it fits perfectly with the definition of aesthetic idea as the only possible exhibition of the ideas of the reason.